2015
DOI: 10.2478/aoa-2014-0010
|View full text |Cite
|
Sign up to set email alerts
|

Annoyance Related to Wind Turbine Noise

Abstract: A questionnaire inquiry on response to wind turbine noise was carried out on 361 subjects living in the vicinity of 8 wind farms. Current mental health status of respondents was assessed using Goldberg General Health Questionnaire GHQ-12. For areas where respondents lived, A-weighted sound pressure levels (SPLs) were calculated as the sum of the contributions from the wind power plants in the specific area.Generally, 33.0% of respondents were annoyed outdoors by wind turbine noise at the calculated A-weighted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 13 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…Also, 67% reported that the sound was louder downwind when the wind was strong vs 18% who reported that it was less loud, and 40% thought the sound was louder at night while 22% thought it was less loud. In the Polish study [17] 40% of all respondents could hear the noise more clearly than usual when the wind was blowing from turbine towards their dwelling, and only 6% when the wind was from the opposite direction. The noise was more clearly heard when a rather strong wind was blowing (47%) and during warm summer nights (31%).…”
Section: Audible and Temporal Characteristics Of Wind Turbine Soundmentioning
confidence: 93%
See 1 more Smart Citation
“…Also, 67% reported that the sound was louder downwind when the wind was strong vs 18% who reported that it was less loud, and 40% thought the sound was louder at night while 22% thought it was less loud. In the Polish study [17] 40% of all respondents could hear the noise more clearly than usual when the wind was blowing from turbine towards their dwelling, and only 6% when the wind was from the opposite direction. The noise was more clearly heard when a rather strong wind was blowing (47%) and during warm summer nights (31%).…”
Section: Audible and Temporal Characteristics Of Wind Turbine Soundmentioning
confidence: 93%
“…In a field study amongst Polish residents [17] the most frequent verbal descriptors of noise characteristics were "rustling" (28%), "swishing" (27%) and 'quiet' (23%). In Canadian and Japanese wind turbine noise field studies no question on the sound character was included.…”
Section: Audible and Temporal Characteristics Of Wind Turbine Soundmentioning
confidence: 99%
“…A questionnaire to respond to noise from wind turbines was administered to 361 subjects living near 8 wind farms [48]. A general health questionnaire assessed the respondents' current mental health status.…”
Section: Structural Factors Of Energy Efficiency-review Of Sourcesmentioning
confidence: 99%
“…Over the years, a considerable amount of studies has been implemented to examine the impacts on local residents' health results from turbine noise, with indicators including visual effect, self-control of noise, physical condition, attitude, and subjective opinions, as well as sensory acuity and sensitivity have been defined [7,11,12]. Among these indicators, individual sensitivity to turbine noise is a highly controversial topic, as some survey-based studies indicate that people living in higher noise-exposed areas are more sensitive to turbines noise [13,14], while others also argued that it is indeed the people living in lower noise-exposed areas who have higher wind turbines noise sensitivity [15,16]. Visibility of wind turbines was also found to be an important factor affecting the assessment of turbine noise.…”
Section: Introductionmentioning
confidence: 99%